2017
DOI: 10.1155/2017/8530261
|View full text |Cite
|
Sign up to set email alerts
|

Panretinal Photocoagulation Using Short-Pulse Laser Induces Less Inflammation and Macular Thickening in Patients with Diabetic Retinopathy

Abstract: We compared the effect of panretinal photocoagulation (PRP) using short-pulse laser (SPL) and conventional laser, regardless of the number of spots, in terms of their effect on the progression of diabetic macular edema (DME) and anterior flare intensity (AFI) in patients with high-risk nonproliferative diabetic retinopathy (non-PDR). Forty-two eyes of 42 patients were subjected to PRP using the conventional argon laser (Conv group) or SPL (SPL group). CRT and AFI levels in the SPL group were significantly lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…The degree of pain for the patient and the expansion of the coagulation zone were also reduced compared to those in the conventional laser. In addition, it has been reported that the amount of inflammatory cytokines induced following its treatment was lower than that of the conventional methods [77]. Finally, the operation time could be shortened, a significant point during the surgery [78,79].…”
Section: Treatment For Drmentioning
confidence: 99%
“…The degree of pain for the patient and the expansion of the coagulation zone were also reduced compared to those in the conventional laser. In addition, it has been reported that the amount of inflammatory cytokines induced following its treatment was lower than that of the conventional methods [77]. Finally, the operation time could be shortened, a significant point during the surgery [78,79].…”
Section: Treatment For Drmentioning
confidence: 99%
“…Recently, short-pulse pattern scan laser system (PASCAL® Streamline, Topcon Medical Laser systems, Santa Clara, CA, USA) has been developed [ 6 , 7 ], and it is known that short-pulse laser treatment is quicker, generates less heat, and is less painful to eyes than the conventional laser treatment [ 6 ]. Moreover, some reports indicate that short-pulse laser treatment induces less inflammation, fewer inflammatory cytokines in the sensory retina, and less macular thickening in patients with diabetic retinopathy than the conventional pulse duration [ 2 – 4 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, laser photocoagulation may be an important factor in the postoperative anterior inflammation. 11 18 19 Actually, our data showed that there was a positive correlation between the number of laser shots and AFI in the VIT group. In contrast, this significant relationship was not observed in the IVTA+VIT group, which indicated that IVTA potentially could inhibit inflammation after surgery even if the number of laser spots was relatively greater.…”
Section: Discussionmentioning
confidence: 56%